The Rationality of Early Exercise Decisions: Evidence from the S&P 100 Index Options Market - Diz, Fernando; Finucane, Thomas J. (Review of Financial Studies, 1993)
This study provides a comprehensive empirical analysis of the early exercise history of S&P 100 put and call option. Even though the S&P 100 index option market is generally considered to be the most efficient options market in the world, we show that many exercise decisions are inefficient because they occur when recorded bids are greater than exercise values. Due to market imperfections, some of the cases of inefficient exercise are still rational, but we show that a substantial number of these decisions are clearly irrational since it would have been possible to realize a larger riskless net cash flow by selling. Unlike previous studies of early exercise, our tests of efficiency and the rational decisions that presumably lead to efficient markets are model independent. We also provide evidence concerning the relative significance of dividends and the wild card to index option pricing models, and introduce and document the importance of the option to exercise and avoid the indirect costs of the spread. We also find evidence of a significant day-of the-week exercise effect, and present some likely explanations for that effect.